Small ubiquitin‐like modifier/sentrin‐specific peptidase 1 associates with chemotherapy and is a risk factor for poor prognosis of non‐small cell lung cancer. Issue 9 (24th July 2018) - Liu, Keyuan; Zhang, Jing; Wang, Hao
Abstract : Background: SUMO/sentrin‐specific peptidase 1 (SENP1) was associated with radioresistance of cancer cells and was upregulated in non‐small cell lung cancer (NSCLC). This study was to investigate the association of SENP1 with resistance of NSCLC tumor to chemoradiotherapy. Methods: Sentrin‐specific peptidase 1 expression profile was detected using the immunohistochemistry and quantitative real‐time PCR (qRT‐PCR) analyses. The relative expression level of SENP1 mRNA was detected using qRT‐PCR. The response to chemoradiotherapy was evaluated according to the Response Evaluation Criteria in Solid Tumors. Results and Conclusion: When compared with adjacent non‐tumor tissues, the overexpression of SENP1 mRNA and protein in NSCLC tumor tissues was determined using qRT‐PCR and immunochemistry. Based on the chemoradiotherapy response rate, we found that NSCLC patients with higher SENP1 expression showed lower rates of complete response and higher partial and non‐response rate to chemoradiotherapy. In the overall survival analysis, we found patients with high SENP1 expression showed significant shorter survival time compared with those with low SENP1 expression. In the multivariate Cox regression model, we found SENP1 overexpression, TNM stage, and lymph metastasis were independent risk factors for poor prognosis of NSCLC. SENP1 overexpression contributed to chemoradiotherapy resistance of NSCLC. The overexpression of SENP1 could be used as a risk factor for the poor prognosis of NSCLC.